(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Purpose. This article describes the formation of a hybrid form of an electronic textbook in legal education, the essence of online education, theoretical and practical foundations for the correct use of available sources of information for electronic textbooks. Methodology. The article uses methods of source analysis, pedagogical experiment and comparative analysis to determine the advantages of an electronic textbook integrating search engines and open access sites. Results. The problems of using electronic textbooks in legal education are analyzed. Studies, scientific works, experiments of foreign scientists have been studied and analyzed, and proposals for implementation in Uzbekistan are given. The existing systems are recommended for the implementation of the virtual environment in the management system of the legal education process. Conclusion. From these results it is clear that with the help of these systems, students can achieve such qualities as the formation and development of research, information and professional competence.